Aprendizagem ativa na educação infantil: transformando a sala de aula em um espaço de criatividade - Freitas, Eloá Fernanda de (Universidade do Vale do Rio dos Sinos, 2019)
This article, entitled "Active Learning in Early Childhood Education: Turning the Classroom into a Space for Creativity", addresses the importance of working with active methodologies in early childhood education, using it as a tool to foster the learning process, making the classroom a space designed for creativity. The main objective is to reflect on how classroom space can become an educative element and facilitator for learning, since innovation is present in education and suggests new practices. The Jesuit Education Network recognizes this need to renew and innovate teaching to meet the challenges of today, prioritizing the overall development of the person, transforming their teaching centers into centers of meaningful learning for students.
Keywords: Aprendizagem ativa; Movimento Maker; Projeto Educativo Comum; Sala de aula; Active learning; Motion Maker; Common Educational Project; Classroom